Techniques of Excavation and Documentation in the Terramara of St. Rosa of Poviglio, XXX Campaign: The Experience of Two Postgraduate Students (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
The excavations of terramara S. Rosa of Poviglio (RE), of the Middle-Late Bronze Age, arrived at the XXX campaign, have gained a large knowledge of the site, thanks to the contribution of many collaborators with different academic background. Multidisciplinarity of the research and attention at publishing and promotion of the area arise as essential elements of the project. It is worth to mention also the close-knit and competent team and the logistic organization well strengthened in time.
Keywords: terramara; S.Rosa; Poviglio; Middle-Late Bronze Age